Securing your business with CISCO ASA and PIX firewalls - Abelar, Greg (Cisco ; Pearson Education [distributor], 2005)
Protect critical data and maintain uptime with Cisco ASDM and Cisco Security Agent Understand how attacks can impact your business and the different ways attacks can occur Learn about the defense-in-depth model for deploying firewall and host protection Examine navigation methods and features of Cisco ASDM Set up Cisco ASA, PIX Firewall, and ASDM hardware and software Use the Cisco ASDM startup wizard to safely connect your network to the Internet and securely add public devices such as mail and web servers to your network Authenticate firewall users and users of public web servers Filter traffic and protect your network from perimeter attacks Deploy Cisco Intrusion Prevention System (IPS) to provide more granular traffic inspection and proactive threat response Stop attacks launched at the desktop by deploying Cisco Security Agent Extend the defense-in-depth model to remote users through IPSec virtual private networks (VPN) Enhance your security posture through proper security management Understand the advanced features available in the Cisco PIX version 7 operating system Recover from software failure with Cisco PIX version 7 Many people view security as a "black-box-voodoo" technology that is very sophisticated and intimidating. While that might have been true a few years ago, vendors have been successful in reducing the complexity and bringing security to a point where almost anyone with a good understanding of technology can deploy network security. Securing Your Business with Cisco ASA and PIX Firewalls is an extension of the work to simplify security deployment. This easy-to-use guide helps you craft and deploy a defense-in-depth solution featuring the newly released Cisco® ASA and PIX® version 7 as well as Cisco Security Agent host intrusion prevention software. The book simplifies configuration and management of these powerful security devices by discussing how to use Cisco Adaptive Security Device Manager (ASDM), which provides security management and monitoring services through an intuitive GUI with integrated online help and intelligent wizards to simplify setup and ongoing management. In addition, informative, real-time, and historical reports provide critical insight into usage trends, performance baselines, and security events. Complete with real-world security design and implementation advice, this book contains everything you need to know to deploy the latest security technology in your network. Securing Your Business with Cis...